Eiríkur Bergmann Einarsson: Iceland and the International Financial Crisis: Boom, Bust and Recovery - Conrad, Maximilian (Stjórnsýslustofnun, 2014)
The book is a highly interesting read particularly for international audiences hoping to get a deeper insight not only into the causes and consequences of the collapse of the three banks, but more importantly also into the histo rical, political - cultural, and no less into the political - psychological background and dimension of the crisis. The chapters presenting Iceland’s economic history as well as the rise and fall of the Icelandic banks therefore present a very useful summary o f the existing literature on the subject, although the interested reader could also have hoped for a more diverse selection of sources.